Infection Level of Pathogenic Bacteria in Pork at Traditional Market in Denpasar - Ni Nyoman Puspawati (Master Program of Food Science and Technology, Faculty of Agricultural Technology, Udayana University, 2015)
The aim of the research were to achieve scientific information about the infection level of bacteria found in pork meat and to acquire the information of the sanitation level of the meat stall in traditional market around Denpasar. This research used survey method in sampling before being analyzed in Laboratorium. There are 16 traditional market in Denpasar, based on the minimum survey of sampling which is 30%, 4 market has chosen for sample source. The parameter of this research is total of Coliform, total of E.coli and Salmonella sp, also the sanitation level and hygiene of the butcher using questionare. The result of the research showed that the infection level of Coliform in pork found in the market has been over the limit of SNI which is on the morning market of Badung is (2.5 ± 1.7) x 105 cfu/cm2, Impres Sanglah market is (7.3 ± 1.2) x 104 cfu/cm2, Ubung market is (2.9 ± 4.1) x 104 cfu/cm2 and Kreneng market is (1.4 ± 1.5) x 104 cfu/cm2. The infection level of E. coli found in pork is over the limit of SNI, which is on the morning market of Badung is (5.7 ± 8.2) x 104cfu/cm2, Impres Sanglah market is (2.3 ± 2.8) x 104cfu/cm2, Ubung market is (1.4 ± 1.6) x 104 cfu/cm2 and Kreneng market is (8,3 ± 1,1) x 103cfu/cm2. The infection level of Salmonella sp found in pork is over the limit of SNI, which is Impres Sanglah market (6.6 ± 1.1) x 103 cfu/cm2,on the morning market of Badung is (5.6 ± 7.5) x 103 cfu/cm2, Ubung market is (5.2 ± 6.8) x 103 cfu/cm2 and Kreneng market is (3.2 ± 3.9) x 102 cfu/cm2. The source of contamination come from the surroundings of the butcher stall in the market that is lack of hygiene and sanitation standard